Answer:
y = 1/2x -3
x=-2 ⇒ y = -4
x=-1 ⇒ y = -3.5
x=0 ⇒ y = -3
x=1 ⇒ y = -2.5
x=2 ⇒ y = -2
Step-by-step explanation:
Hi, to answer this question we have to isolate y:
x - 2y = 6
-2y =6-x
y = (6-x)/-2
y = -3+1/2x
y = 1/2x -3
Now, we have to create a table with the next values (see attachment)
x=-2 ⇒ y = 1/2x -3 = 1/2(-2)-3= -4
x=-1 ⇒ y = 1/2x -3 = 1/2(-1)-3= -3.5
x=0 ⇒ y = 1/2x -3 = 1/2(0)-3= -3
x=1 ⇒ y = 1/2x -3 = 1/2(1)-3= -2.5
x=2 ⇒ y = 1/2x -3 = 1/2(2)-3= -2
Feel free to ask for more if needed or if you did not understand something.
<span>given that P(x) --->p(x+6)+3
</span>
∴ x will become x+6
and P(x+6) will become P(x+6)+3
<span />
So, The graph of [p(x+6)+3] will be the same as the graph of [p(x)] but shifted 6 units to the left then shifted 3 units up
OR by another words, we need to make axis translations from (0,0) to (-6,3)
Answer:
-34 -7a
Step-by-step explanation:
–34–23a+16a
Combine like terms
-34 -7a